Penggunaan Metode Giving Questions And Getting Answer Terhadap Keaktifan Belajar Siswa SMA - Lissa Lissa (Universitas Muhammadiyah Prof. Dr. Hamka, 2017)
The method of learning in the field was not varied and innovative and the teacher does not spur the involvement of the students, so it affects the students' learning activeness. Methods that can involve the activities of the student and make the active student was Giving Question and Getting Answer method. This study aims to determine the effect of Giving Question and Getting Answer method on the students' learning activity on ecosystem material. This type of quantitative research with True-Experimental Desigen research design. The population in this study was all students of class X MIPA in SMA Negeri 1 Krangkeng in academic year 2016/2017 which amounted to 166 students. The sample of research consisted of 2 classes that is class X MIPA 1 (experiment) which amounted to 30 students and class X MIPA 2 (control) which amounted to 29 students obtained by cluster random sampling technique. The research instrument used is observation sheet of students' learning activity. From the data analysis that has been done, the average score of the learning activity of the experimental class students using Giving Question and Getting Answer method is 31.97 and the average score of students' learning activity learning using control class using the conventional method is 29.40. Hypothesis test used is t test and obtained tobs = 4,486 and ttable = 1,672. Because tobs> ttable, then Ho is rejected. This means that the use of Giving Question and Getting Answer method has an effect on students' learning activeness.